2020
DOI: 10.4103/ijmr.ijmr_1788_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-demographic profile & hospital outcomes of COVID-19 patients admitted at a tertiary care centre in north India

Abstract: Background & objectives: In December 2019, a novel coronavirus (SARS-CoV-2) emerged in China and rapidly spread globally including India. The characteristic clinical observations and outcomes of this disease (COVID-19) have been reported from different countries. The present study was aimed to describe the clinico-demographic characteristics and in-hospital outcomes of a group of COVID-19 patients in north India. Methods: This was a prospective, single-centre collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
93
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 23 publications
25
93
2
Order By: Relevance
“…Another observation was that the median (IQR) time for RT-PCR to become negative in the present cohort was 16 (12)(13)(14)(15)(16)(17)(18)(19) d, a finding similar to the report from Delhi on adult patients [24]. Studies on virological assessment of hospitalized patients with COVID-19 showed persistence of SARS-CoV-2 RNA in nasopharyngeal samples for a duration of about 2 wk [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Another observation was that the median (IQR) time for RT-PCR to become negative in the present cohort was 16 (12)(13)(14)(15)(16)(17)(18)(19) d, a finding similar to the report from Delhi on adult patients [24]. Studies on virological assessment of hospitalized patients with COVID-19 showed persistence of SARS-CoV-2 RNA in nasopharyngeal samples for a duration of about 2 wk [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…We observed that the males comprised an overwhelming majority (82.3%) of our patients This is similar to the data from other South Asian countries like India, Pakistan, Bangladesh, and Iran where the males comprised 60 to 90% of the admitted COVID-19 patients [9][10][11][12]. The male preponderance among the hospitalized patients was less pronounced in countries like the US, UK,China and Indonesia [13][14][15][16].One possible reason for this overwhelming male majority is that most of the COVID-19 patients in our study were migrant workers, and it is usually the adult males who go abroad for work.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the males comprised an overwhelming majority (82.3%) of our patients This is similar to the data from other South Asian countries like India, Pakistan, Bangladesh, and Iran where the males comprised 60 to 90% of the admitted COVID-19 patients [9-12]. The male preponderance among the hospitalized patients was less pronounced in countries like the US, UK,China and Indonesia [13-16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…in a study done among COVID-19 positive patients at a tertiary care institution in North India. (16) Maximum proportion (79.23%) of patients visiting CS-OPD was without any symptoms relevant to COVID-19. This asymptomatic population visiting CS-OPD was mainly consisted of patients coming to the hospital for follow up visits, patient attendants, healthcare workers and individual with travel history to hotspot areas at that point of time.…”
Section: Discussionmentioning
confidence: 96%